Addressing the heterogeneous IT landscape of bioanalytical laboratories to increase efficiency of regulatory reporting and data analysis. (July 2011) - Bittner, Norbert
Modern bioanalytical laboratories are operating heterogeneous IT systems to satisfy process-related data capturing and processing. Whenever a cross-system perspective is desirable, for example, to answer ''quality-by-design''-related questions or populate submission documents, manual processes dominate these organizations. This article discusses the origin of this situation and the typical approach as well as a state-of-the-art approach to resolve cross-system obstacles.